CLRM-08 TARGETING IMMUNE-PAYLOAD TO THE GLIOBLASTOMA TUMOR MICROENVIRONMENT USING A MACROPHAGE-BASED TREATMENT RELYING ON AUTOLOGOUS, GENETICALLY MODIFIED, HEMATOPOIETIC STEM CELL-BASED THERAPY: THE TEM-GBM STUDY (NCT03866109). (5th August 2022) - Eoli, Marica; Farina, Francesca; Gentner, Bernhard; Capotondo, Alessia; Anghileri, Elena; Barcella, Matteo; Brambilla, Valentina; Bruzzone, Maria Grazia; Carrabba, Matteo; Cuccarini, Valeria; d'Alessandris, Giorgio; Meco, Francesco Di; et al.
Abstract: We developed an autologous hematopoietic stem cell-based platform designed to deliver IFNa, by a transcriptional and post-transcriptional control mechanism mediated by miRNA target sequences, specifically into the tumor microenvironment (TME) via Tie-2 expressing monocytes (Temferon). As of Feb 2022, 3 escalating doses of Temferon (0.5-2.0x106/kg) were tested across 15 newly diagnosed, unmethylated MGMT GBM patients assigned to 5 cohorts. Follow-up from surgery is 6–28mo (2–25mo after Temferon). To date, no DLTs have been identified. As expected, 1mo after the administration of the highest tested dose, the hematopoietic system of Temferon-treated patients was composed of up to 30% of CD14+ modified cells. Temferon-derived progeny persisted, albeit at lower levels, up to 18mo (longest time of analysis). Despite the substantial proportion of engineered cells, very low concentrations of IFNα were detected in the plasma and in the CSF, indicating tight regulation of transgene expression. SAEs were mostly attributed to conditioning chemotherapy (infections) or disease progression (seizures). 1SUSAR (persistent GGT elevation) occurred. Median OS is 15mo from surgery. Homing of transduced cells to the tumor was demonstrated by the presence of gene-marked cells in the 2nd surgery specimens of 3 out 4 pts belonging to low dose cohorts. Single-cell RNA seq of the TME highlighted a Temferon signature associated with the induction IFNa responsive genes and macrophage repolarization. Potential long-term benefit with Temferon was identified in a patient from cohort 3, who had PD at D+120 with two distant enhancing lesions, and increased tumor necrosis. 1y following Temferon, with no 2nd-line therapy added, there was approximately 40% reduction in enhancing tumor volume compared to D+180 with a stable clinical and imaging picture thereafter. The results provide initial evidence of Temferon's potential to modulate the TME of GBM patients, and anecdotal evidence for long lasting effects of Temferon in prevention of disease progression.